Intellectual System for Printed Circuit Board Manufacture Based on Mirae Mx-200 - Sineglazov , Victor; Plodystyy, Bogdan (Electronics and Control Systems, 2021)
It is considered the main disadvantages of printed circuit boards manufacture based on the Mirae Mx-200 system. In order to reduce the level of manufacturing defects and increase productivity, it is proposed to include an intelligent unit based on the YOLO neural network in the system, which is implemented by an additional Raspberry controller included in the system. The YOLO neural network is used to process images obtained from an additionally installed video camera, which monitors the production process. In this work, based on the use of the solution to the classification problem, the problem of decision support is formulated and solved. As a result, the operations (actions) that need to be taken are determined: automatic centering, reset, cancel, etc. Using emulation with additional microcontroller connections, the problem of limited installer resources and the implementation of more complex algorithms in the installer’s work is solved.